Comparison of fecal hormone extraction methods and analysis on reproductive hormones in female Malayan tapirs - Ruslan, Muhammad Najib (2018)
Non-invasive hormone monitoring provides an important tool to optimize breeding strategies of wildlife species including tapir in captive managements. Previous studies stated that tapir sp. would have been excreted low amount of steroids (progesterone and 17β-oestradiol) in their feces. In addition, there is still no standardized fecal extraction protocol for Malayan Tapir. Therefore, it is important to detect that low amount of hormones (progesterone and 17β-oestradiol) through several fecal extraction protocols in Schwarzenberger et al. (1996a) (Method A and B), Brown et al. (2001) (Method C), and Shutt et al. (2012) (Method D). The fecal extraction method provides differences in the steps of the method and solvents that used to extract the steroid hormones. Fecal samples were collected from four female Malayan Tapir (N=4) at Sungai Dusun Wildlife Reserve (n=2), Zoo Taiping (n=1) and Zoo Negara (n=1), Malaysia. Results from Liquid Chromatography Mass Spectrometry (LCMS) confirmed the presence of progesterone but not for 17β-oestradiol in fecal samples. Meanwhile, results from Enzyme Linked Immunosorbent Assay (ELISA) showed that there was not a significant difference between all methods in progesterone and its relation to reproductive status (p>0.05). In contrary, there was significant difference between methods in 17β-oestradiol and its relation to reproductive status (p<0.05). These results suggest that, validating the progesterone immunoassay is needed as it might underestimate the actual progesterone concentration. Besides, all extraction protocols for 17β-oestradiol resulted in different concentration range between nonpregnant and pregnant animals. Nevertheless, fecal 17β-oestradiol analysis could be suitable for determining pregnancy status in female Malayan Tapirs.